THE QUEST FOR CONSTITUTIONALISM IN SOUTH AFRICA' - M. Muravyeva (BRICS Law Journal)
Reviewed book: Corder Hugh, Veronica Federico, and Romano Orrù (eds.) The Quest for Constitutionalism: South Africa Since 1994 (Ashgate Publishing, Ltd. 2014).